Middle East bank and their challenge operation in Malaysia: A case study on Kuwait Finance House Malaysia Berhad - Shuib, Mohd Sollehudin; Sulaiman@Mohamad, Ahmad Azam; Mohamad, Mohammad Taqiuddin (Academic Journals, 2011)
This research attempts to understand the history of first foreign Islamic bank that operate in Malaysia.The bank was Kuwait Finance House Malaysia Berhad (KFHMB).The focus is on how KFHMB implement musharakah mutanaqisah concept for home financing product.This paper will discus on how this syariah concept run on Islamic home financing product, their advantages, issues and challenges that was face by KFHMB. This research also focuses on determining Musharakah Mutanaqisah itself.This research shows that home financing through musharakah mutanaqisah is a new product in Malaysia, offered from 2005 by KFHMB. Musharakah Mutanaqisah was a hybrid contract and created by some element like ijarah, al-bay‘, musharakah. This research also shows that this respondent banks offer the product with their own style in certain part in the same time related with Malaysia buying and selling house tradition.This situation affected institutions from different background and how they run their product. This study also proposes how KFHMB solve the issues and challenges from product offering.